Using geographic information systems to inform the public health response to COVID‐19 and structural racism: The role of place‐based initiatives. Issue 6 (21st December 2021) - Siegal, Rachel; Cooper, Haley; Capers, Tiffany; Kilmer, Ryan P.; Cook, James R.; Garo, Laurie
Abstract: Black communities have been disproportionately impacted by the syndemic of COVID‐19 and structural racism. Place‐based initiatives (PBIs) are well‐positioned to respond to this syndemic. This study sought to highlight disparities in access to social determinants of health (SDH) between two racially segregated communities, assess residents' needs and measure resource accessibility in one predominantly Black community, and describe the PBI's response. We measured racial disparities in access to SDH before COVID‐19 using an SDH Index. We assessed participants' needs using a needs assessment and documented resource availability. A Geographic Information System (GIS) was used to measure resource accessibility. Results show inequities in access to SDH between the two communities before COVID‐19. Following the onset of COVID‐19, unemployment and food insecurity were higher in the predominantly Black community relative to the US population. Available resources did not always align with participants' needs and were less accessible for residents without private transportation. The PBI's response to the syndemic spanned SDH sectors. Inequitable access to SDH may be produced by structural racism and exacerbated by COVID‐19. PBIs are well‐equipped to employ a contextually informed, data‐driven, cross‐sector response to the syndemic.